Blood hormones as markers of training stress and overtraining - Urhausen, A.; Gabriel, H.; Kindermann, W. (Sports Medicine, 1995)
This excellent review covers most features analyzed in blood when attempts are made to associate biochemical factors and overtraining. A distinction is made between overreaching, short-term accumulated fatigue that can be erased by longer than normal rest periods, and overtraining, a result of continued exposure to excessive training stimuli without adequate recovery. Overtraining is generally characterized by a decrease in performance when training load is maintained or increased, enhanced fatiguability, disruptions to sleep, rest, and social behaviors, and complaints of poor well-being. Implications: - The testosterone/cortisol ratio indicates the physiological strain of training load rather than overtraining syndrome. - The frequency of competitions or training sessions with higher anaerobic lactic demands, should be carefully limited in order to prevent overtraining syndrome. - The role of hormones in the recovery phase and their effects on the receptor and intracellular level remain to be better established. - External and measurement factors influence hormonal blood levels and need to be controlled very well before any test results can be considered for the diagnosis of overtraining.